Application of hydrologic-tracer techniques to the Casargiu adit and Rio Irvi (SW-Sardinia, Italy): Using enhanced natural attenuation to reduce extreme metal loads. (September 2018) - De Giudici, Giovanni; Medas, Daniela; Cidu, Rosa; Lattanzi, Pierfranco; Podda, Francesca; Frau, Franco; Rigonat, Nicola; Pusceddu, Claudia; Da Pelo, Stefania; Onnis, Patrizia; Marras, Pier Andrea; Wanty, Richard B.; et al.
Abstract: Hydrologic tracer techniques were applied to Rio Irvi (SW Sardinia), a stream affected by mine drainage, allowing the calculation of stream discharge and metal loads and comparison to other streams. The calculated discharge showed a continuous increase from near 21.2 L/s to 29.1 L/s. Cumulative loads of mine-related constituents, including the Casargiu adit inflow, were large, with more than 9900 kg/day of SO4 2−, 2370 kg/day of Zn, 550 kg/day of Fe and 172 kg/day of Mn. The greatest measurable inflow source of metals, other than the Casargiu adit, was an acidic tributary (L4), but most sources of instream metal load were related to dispersed groundwater inflows. Some of those groundwater inflows were related to non-flowing tributaries. Calculations of the cumulative instream metal load, excluding the Casargiu adit inflow, indicated increases of 1250 kg/day for SO4 2, 858 kg/day for Zn -, 137 kg/day gain for Fe and 60 kg/day for Mn. Rio Irvi Zn load was extreme for a stream of this size and discharge. A comparison with two other mine-affected rivers in Sardinia indicated the loading in Rio Irvi was two to three orders of magnitude greater. This difference was attributed to different geochemical conditions, but also to a lack of a biogeochemical barrier like that seen to be acting along and below the riverbed in Rio San Giorgio. Several years of intense vegetation growth in the river bed of Rio San Giorgio created a biogeochemical barrier to metal loading, and the cumulative Zn load there was near 8 kg/day, despite being a drainage with a greater mass of mine wastes to contribute to the load. Highlights: Hydrologic tracer techniques were applied in Rio Irvi (Sardinia, Italy). Cumulative instream loads were exceptionally large for SO4 2−, Zn and Fe. A comparison with two other mine-affected rivers was performed. Rio Irvi is characterised by a lack of a biogeochemical barrier.